HUBUNGAN TINGKAT PENDIDIKAN DAN PENGETAHUAN IBU TERHADAP PEMAKAIAN ALAT KONTRASEPSI DI WILAYAH KELUARGA BINAAN KESEHATAN FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2016 DI KECAMATAN MEDAN JOHOR SUMATERA UTARA TAHUN 2019 - TOHRI TOHIR; HEPPY JELITA SARI (LP2MTBM MAKARIOZ, 2021)
Contraception is an effort to prevent pregnancy, these efforts can be temporary, or can also be permanent. From year toyear the population in Indonesia is increasing. Contraceptive use is influenced by the level of education and level ofknowledge. To find out the relationship between the level of education and mother's knowledge on the use of contraceptivesin health fostered families, Faculty of Medicine, University of Muhammadiyah, North Sumatra Class 2016 in Medan JohorDistrict, North Sumatra, 2019. This research is descriptive analytic with cross sectional design and total sampling.Forty-five mothers. 26 people (57.8%) did not use contraception and 19 people (42.2%) did not use contraception. From theanalysis data, P = 0,000 (P <0.05) shows that there is a significant relationship between education level and mother'sknowledge of contraceptive use. Mother's level of education and knowledge can influence the use of contraceptives.